Evaluation of global techno-socio-economic policies for the FEW nexus with an optimal control based approach - Nisal, Apoorva; Diwekar, Urmila; Hanumante, Neeraj; Shastri, Yogendra; Cabezas, Heriberto; Rico Ramirez, Vicente; Rodríguez-González, Pablo Tenoch (Frontiers in Sustainability, 2022)
Inordinate consumption of natural resources by humans over the past century and unsustainable growth practices have necessitated a need for enforcing global policies to sustain the ecosystem and prevent irreversible changes. A global model has been developed recently with a focus on sustainability for the Food-Energy-Water (FEW) Nexus. This model is a 15-compartment model with components for the food-web, microeconomic framework, energy, industry and water sectors, and humans. %It was validated based on historical data for global sectors and can predict population, global and regional water stress, GHG emissions, and the gross domestic product (GDP) for the next century. The analysis of several scenarios to evaluate sustainability with this model showed that indiscriminate human consumption would lead to collapse of several resources in the future. Such circumstances warrant a study where sustainability is attained. An optimal-control theory based approach is presented here to evaluate sustainability by employing multiple global indicators and controlling them. The Sustainable Systems Hypothesis proposes that sustainability can be achieved by limiting the human burden on the environment so as to not exceed the biocapacity, conservation of trophic and functional integrity of the ecosystem, adequate economic production to exceed the consumption, certain quality of human existence, sustainable use of energy resources and finally, and maintenance of system order and self-organization over time. These conditions are captured through several sustainability indicators: Fisher Information, Green Net Product, Ecological Buffer, and carbon dioxide emissions, nitrous oxide emissions, and the global water stress. The optimal control model assesses the multiple objectives. This study aims to look at the three crucial areas towards sustainability- ecological, economic, and social well-being. Thus, various policy options %such as regulatory, economic, or technological parameters are assessed as control variables, and a multivariate optimal control approach for global sustainability aimed at providing policy recommendations is explored. This study shows that optimizing for the Fisher Information based objective is adequate to attain sustainability and manage the other objectives under consideration. Further, the results show that cross-dimensional policy interventions are necessary for sustainability and to observe positive impacts at scale.